Analisis Perbandingan Lembaga Asuransi Syariah dan Asuransi Konvensional : Sebuah Tinjauan Litelatur: Asuransi Syariah, Asuransi, Tabarru’, Sharing Of Risk, Hukum Islam - Ilman Miftahul Fauzi; Iqbal Abdul Azis; Fahmi Nurfatwa; Muhammad Gesta Nugraha Fauzi; Joni; Raihani Fauziah (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
The increasing demand for insurance products in Indonesia, especially among the Muslim majority, has prompted the need for an in-depth study of the differences between sharia insurance and conventional insurance. This study uses a qualitative method with a literature review approach, where data sources are obtained from academic literature, regulations, and relevant national journal articles. The analysis was conducted through content analysis to identify the fundamental similarities and differences in terms of legal basis, fund management mechanisms, fund ownership principles, and risk sharing systems. The results of the study show that sharia insurance is based on the Qur'an, Hadith, ijma, and qiyas, with the main principle of mutual assistance (ta'awun) and a risk-sharing mechanism through tabarru' funds that remain the collective property of the participants. Conversely, conventional insurance is rooted in Western positive law with the principle of transfer of risk, where the premiums paid become the full property of the company, while the investment profits are fully controlled by the insurer. In addition, conventional insurance practices have the potential to contain elements of gharar, maisir, and riba, which are not in accordance with Islamic law. The conclusion shows that sharia insurance is not merely a financial protection instrument, but also a form of social solidarity and justice that is more in line with the needs of the Muslim community in Indonesia.